Multidimensional Approach for Investigating the Effects of an Antibiotic–Probiotic Combination on the Equine Hindgut Ecosystem and Microbial Fibrolysis - Collinet, Axelle; Grimm, Pauline; Julliand, Samy; Julliand, Véronique (Frontiers in Microbiology, 2021)
The equine hindgut ecosystem is specialized in dietary fibers’ fermentation to provide horses’ energy and contribute to its health. Nevertheless, antibiotics are known to disrupt the hindgut microbiota, affect the fibrolytic activity of bacteria and the intestinal immune balance, leading to diseases. This in vivo study used a general and comprehensive approach for characterizing the hindgut ecosystem of 9 healthy horses over 28 days in response to a 5-days challenge with oral trimethoprim-sulfadiazine (TMS), with a special emphasis on microbial fibrolytic activity and the host immune response. Horses were supplemented with two doses of Lactobacillus acidophilus, Ligilactobacillus salivarius (formely Lactobacillus salivarius) and Bifidobacterium lactis blend or a placebo in a 3  3 Latin square design. Changes in fecal microbiota were investigated using 16S rRNA sequencing. Clostridioides difficile was quantified in feces using quantitative polymerase chain reaction. Anaerobic microbiological culture was used to enumerate functional bacterial groups (cellulolytic, amylolytic and lactic acid-utilizing). The environmental dimensions were assessed by measuring the concentrations of volatile fatty acids (VFAs) and lactic acid using biochemical methods, and changes in pH and dry matter weight. Systemic and local inflammation were evaluated by determination of cytokines and immunoglobulin (Ig)A concentration in the serum and secretory IgA (SIgA) concentrations feces using immuno-enzymatic methods. Oral TMS treatment strongly altered the whole hindgut ecosystem by 2 days after the first administration. Bacterial diversity decreased in proportion to the relative abundance of fibrolytic genera, which coincided with the decrease in the concentration of cellulolytic bacteria. At the same time, the composition of microbiota members was reorganized in terms of relative abundances, probably to support the alteration in fibrolysis. C. difficile DNA was not found in these horses, but the relative abundances of several potential pathobiont genera increased. Two days after the first TMS administration, fecal concentrations of VFAs and SIgA increased in parallel with fecal water content suggesting an alteration of the integrity of hindgut mucosa. Recovery in bacterial composition, functions and immune biomarkers took 2-9 days after the end of TMS administration. Supplementation with this bacterial blend did not limit bacterial alteration but might have interesting mucosal immunomodulatory effects.